2004
DOI: 10.1161/01.str.0000147965.52712.fa
|View full text |Cite
|
Sign up to set email alerts
|

Statins in Stroke Prevention and Carotid Atherosclerosis

Abstract: Background and Purpose-Previously published meta-analyses exploring the effect of statins on stroke incidence included 20 000 patients and found a 2% to 30% risk reduction. It is not clear whether this is attributable to low-density lipoprotein-cholesterol (LDL-C) reduction. Statin trials have now included Ͼ90 000 patients. We have determined the effect of statins and LDL-C reduction on stroke prevention Summary of Review-We performed a systematic review and meta-analysis of all randomized trials testing stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
440
1
35

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(491 citation statements)
references
References 73 publications
15
440
1
35
Order By: Relevance
“…In the present study, both longitudinal and cross-sectional analyses convincingly excluded CHD and microvascular disease from the causal pathway for depression, whereas CVD was implicated in the cross-sectional study. Second, there is increasingly strong evidence that elevated cholesterol levels are an independent risk factor for ischaemic stroke [42]. Finally, it is known that disability is a risk factor for depressive disorders [43] and we have demonstrated that both stroke and PAD are important predictors of ADL disability in diabetes [28].…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, both longitudinal and cross-sectional analyses convincingly excluded CHD and microvascular disease from the causal pathway for depression, whereas CVD was implicated in the cross-sectional study. Second, there is increasingly strong evidence that elevated cholesterol levels are an independent risk factor for ischaemic stroke [42]. Finally, it is known that disability is a risk factor for depressive disorders [43] and we have demonstrated that both stroke and PAD are important predictors of ADL disability in diabetes [28].…”
Section: Discussionmentioning
confidence: 72%
“…Significant or nearly significant risk reduction of CVD was found for LDL-C 133.4 mg/dL, non-HDL-C 160.8 mg/dL, and LDL-C/ HDL-C ratio 2.0. The benefit of statin therapy against CVD has been well established by numerous large-scale studies [21][22][23][24][25][26][27][28][29] and meta-analyses 30,31) that have also suggested LDL-C target levels used by current guidelines and showed that non-HDL-C and LDL-C/HDL-C are associated with CVD risk. The ATP guidelines 3) state that non-HDL-C is a secondary target, and the level is set by adding 30 mg/dL to LDL-C target levels ( 130 mg/dL for moderate/ moderately high risk, 160 mg/dL for low risk).…”
Section: Discussionmentioning
confidence: 99%
“…Large randomized trials have demonstrated that statins significantly reduce the risk of MI and cardiovascular mortality [27][28][29][30][31], with a magnitude that is greater than expected based on LDL-C reduction alone. In addition, meta-analyses suggest that statins may reduce the risk of stroke to a greater extent than expected based on cholesterol lowering, and more than non-statin lipid lowering therapy [32][33][34]. This suggests that other factors, such as statin-induced hsCRP reduction, may have a role to play in reducing cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%